Avaliação de metaloestrógenos em cabelo de mulheres com câncer de mama por LA-ICP-MS - Rubin, Ana Caroline Vedovato (2021)
In this work, the relationship of metalloestrogens (Al, Sb, As, Ba, Cd, Cr, Co, Cu, Pb, Hg, Ni, Se, Sn, V, and Zn) with breast cancer in women with age around 59 years. Laser ablation coupled to inductively coupled plasma mass spectrometry (LA-ICP-MS) was used to evaluate the changes of these elements along a hair strand while ICP-MS and inductively coupled plasma optical emission (ICP OES) was used to determine elements concentration in hair after sample decomposition. Scanning electron microscopy (SEM) and LA-ICP-MS were used to evaluate the effect on hair washing. Hair washing was done according to the procedure recommended by the International Atomic Energy Agency (IEAE). Hair strands were fixed on a glass slice with the aid of double-side tape and then analyzed. Hair samples without washing were analyzed in the same way. Changes in hair morphology were observed by the analyses with SEM after hair washing, while no changes in element concentration were observed when hair strands were analyzed by LA-ICP-MS after washing. For hair analysis by LA-ICP-MS, laser ablation conditions were fixed to 50 μm, 80 μm s-1 and 26.7 J cm-2, for the spot size, laser speed and ablation energy, respectively. Operational conditions of the ICP-MS instrument were adjusted in order to achieve the best sensitivity. Calibration in LA-ICP-MS was performed by using an internal standard (sulphur in the form of l-cysteine) and filter paper disc (17 mm diameter) as support of the analytes and internal standard. The way to add standard and internal standard solution to the filter paper was evaluate where the best results were achieved by the addition a mixture of the standard solution plus internal standard solution. For ICP-MS and ICP OES analyses, samples were decomposed with nitric acid and heating with the aid of microwave energy. From the analyzes by ICP-MS, ICP OES, and LA-ICP-MS it was observed that the concentrations of the elements in the samples varied, with Ba being the element present in the highest concentration in the samples. By analyzing the results obtained by ICP-MS and ICP OES with statistic tools, it was possible to observe higher concentrations of Ni, Cu, Cd and Sb in hair of women with cancer than women without cancer (Control individuals).